On the relationship between total ozone and atmospheric dynamics and chemistry at mid-latitudes Part 2 - Rieder, Harald; Frossard, L.; Ribatet, M.; Staehelin, J.; Maeder, J. A.; Di Rocco, S.; Davison, A. C.; Peter, T.; Weihs, P.; Holawe, F. (2013)
We present the first spatial analysis of "fingerprints" of the El Nino/Southern Oscillation (ENSO) and atmospheric aerosol load after major volcanic eruptions (El Chichon and Mt. Pinatubo) in extreme low and high (termed ELOs and EHOs, respectively) and mean values of total ozone for the northern and southern mid-latitudes (defined as the region between 30 degrees and 60 degrees north and south, respectively). Significant influence on ozone extremes was found for the warm ENSO phase in both hemispheres during spring, especially towards low latitudes, indicating the enhanced ozone transport from the tropics to the extra-tropics. Further, the results confirm findings of recent work on the connection between the ENSO phase and the strength and extent of the southern ozone "collar". For the volcanic eruptions the analysis confirms findings of earlier studies for the northern mid-latitudes and gives new insights for the Southern Hemisphere. The results provide evidence that the negative effect of the eruption of El Chichon might be partly compensated by a strong warm ENSO phase in 1982–1983 at southern mid-latitudes. The strong west-east gradient in the coefficient estimates for the Mt. Pinatubo eruption and the analysis of the relationship between the AAO and ENSO phase, the extent and the position of the southern ozone "collar" and the polar vortex structure provide clear evidence for a dynamical "masking" of the volcanic signal at southern mid-latitudes. The paper also analyses the contribution of atmospheric dynamics and chemistry to long-term total ozone changes. Here, quite heterogeneous results have been found on spatial scales. In general the results show that EESC and the 11-yr solar cycle can be identified as major contributors to long-term ozone changes. However, a strong contribution of dynamical features (El Nino/Southern Oscillation (ENSO), North Atlantic Oscillation (NAO), Antarctic Oscillation (AAO), Quasi-Biennial Oscillation (QBO)) to ozone variability and trends is found at a regional level. For ...